The return of the Cold War Ukraine, the West and Russia - Black, J. L.; Johns, Michael (Routledge contemporary Russia and Eastern Europe series, 2016)
This book examines the crisis in Ukraine, tracing its development and analysing the factors which lie behind it. The book pays special attention to the often ignored origins of the crisis within Ukraine itself, and the permanent damage caused by the fact that Ukrainians are killing Ukrainians in the eastern parts of the country.